Hydrolysable tannins in Terminalia ferdinandiana Exell fruit powder and comparison of their functional properties from different solvent extracts. (1st October 2021) - Bobasa, Eshetu M.; Phan, Anh Dao Thi; Netzel, Michael E.; Cozzolino, Daniel; Sultanbawa, Yasmina
Highlights: Hydrolysable tannins of Kakadu plum (KP) are important functional food ingredients. The main hydrolysable tannins in KP were corilagin and tri-O-galloyl-β-d -glucose. KP fruit is a rich source of ellagic acid and vitamin C. The hydrolysable tannin-rich extracts showed antimicrobial activity. Abstract: This study identified and quantified hydrolysable tannins (HTs) in Terminalia ferdinandiana Exell (Kakadu plum) fruit, freeze dried powder extracted with 80% aqueous acetone (AA) and 80% aqueous acidified ethanol (AAE), using UHPLC–Q/Orbitrap/MS/MS. The vitamin C and ellagic acid were quantified by UHPLC-PDA. A total of seven HTs were identified: corilagin, 3, 4, 6-tri-O-galloyl-β-d -glucose, elaeocarpusin, chebulinic acid, chebulagic acid, helioscopin B, and punicalagin, with five classified as ellagitannins. The two extracts AA and AAE, comprised of gallic acid (2.5 and 2.2 mg/g DW), punicalagins α and β (2.8 and 1.3 mg/g DW), respectively, and both contained ellagic acid ( 4 g/100 g DW). These extracts showed high antioxidant properties and strong antimicrobial effects against methicillin-resistant Staphylococcus aureus clinical isolate, Staphylococcus aureus, and Shewanella putrefaciens . These results suggest that Kakadu plum fruit is a rich, edible source of ellagitannins, ellagic acid and vitamin C with potential applications in food, cosmetic and nutraceutical industries.